Определение остаточного ресурса и продление срока службы турбоагрегата К-200-130 ст. № 9 Луганской ТЭС - Мамонтов, Н. И.; Пугачева, Т. Н. (НТУ "ХПИ", 2008)
Розглянуті питання, пов'язані з визначенням залишкового ресурсу і продовженням терміну служби ротора і корпусу циліндра середнього тиску турбіни К-200-130. Приведені дані по експлуатації турбіни, по обстеженню елементів ротора і корпусу циліндра середнього тиску. Приведені і запаси тривалої міцності в найбільш навантажених зонах РСТ, в стінці корпусу ЦСТ при різних режимах експлуатації.

The issues has been treated connected of determination of residual resource and extension of term of service of rotor and frame of cylinder of middle pressure of turbine of К-200-130. Information is resulted on exploitation of turbine, on the inspection of elements of rotor and frame of cylinder of middle pressure. Tensions and margins of the long safety are resulted in the most loaded of rotor, in the wall of frame of cylinder of middle pressure at the different condition of exploitation.
Determination of residual resource and extension of term of service of equipment of turbine of K-200-130 of Lugansk
Keywords: паровые турбины; корпусные элементы; тепловые канавки; трещины